Propuesta de manejo de desechos peligrosos generados en los centros de salud públicas y privadas del cantón Valencia año 2019 - Toroche Santacruz, Cristhián Alexander (2019)
The investigation was conducted five public health facilities and six private health canton of Valencia, consisted of developing an integrated management plan for hazardous hospital waste generated by different health agencies. To this end, it was necessary to evaluate the current conditions in the management of hospital waste generated; determine the appropriate management of hospital waste according to the applicable environmental regulations in force; and design the structure of the integrated management plan for hospital waste. The methodology used was based on the following procedure: (i) identification and geographic georeferencing of the evaluated health facilities, through the use of Global Positioning System (GPS) and ArcGIS 10 software.3; (ii) characterization of the hazardous wastes of each health facility through quantification of the volume of daily generation reported in the waste logs; (iii) interviews with medical, administrative and sanitation personnel about the internal management given to the wastes; (iv) audit of legal compliance with internal waste management, based on visits and tours of health centre facilities and subsequent confirmation of compliance with current environmental regulations; (v) preparation of a hazardous waste management plan, including various alternatives and management strategies, as well as the contingencies inherent in management. The results of the study show an average generation of hazardous waste of 305.65 kg/month for the public health service and 219.21 kg/month for the private health service. The categories of hazardous waste in public health centers were: infectious (64.81%), sharpsetters (19.42%) and chemicals (15.77%); while private health centers reported the following wastes: infectious (69.45%), sharpsetters (17.27%) and chemicals (13.28%). In both establishments, inconsistencies were observed in temporary storage, characterized by the lack of perimeter fences and cover in the storage area, lack of covers in containers, incompatibility between the capacity of the container and the volume of waste generated; added to the deficient technical training of those in charge of internal management. Keywords: hazardous waste, health facility, integrated waste management, management plan.